EIFAC Code of practice for recreational fisheries - FAO, Rome (Italy) (Rome (Italy), 2008)
Sumario (En)
Keywords: PESCA; RECURSOS PESQUEROS; PRODUCCION PESQUERA; DESARROLLO PESQUERO; ENTORNO SOCIOECONOMICO